The morning after - Jackson, Lisa (New York : Zebra Books, 2014)
An elusive serial killer dubbed The Grave Robber is loose. Seeing the high-profile murders as her ticket out of small-town Savannah, ambitious reporter Nikki Gillette latches onto the case and onto lead investigator Pierce Reed. Tough-guy police detective Pierce initially sees Nikki's dogged investigations as a mere irritant until evidence turns up indicating that the killer may see Nikki as his prey.
Includes an excerpt from "Tell me!".
Keywords: Journalists -- Georgia -- Savannah -- Fiction; Serial murders -- Georgia -- Savannah -- Fiction; Georgia -- Fiction; Romantic suspense fiction